2010
DOI: 10.1136/adc.2009.177733
|View full text |Cite
|
Sign up to set email alerts
|

An objective study of acid reflux and cough in children using an ambulatory pHmetry-cough logger

Abstract: In children with chronic cough and suspected of having gastro-oesophageal reflux disease, the temporal relationship between acid reflux and cough is unlikely causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 42 publications
(59 reference statements)
0
16
0
1
Order By: Relevance
“…It cannot be overemphasized that pediatric best practice involves both identifying children at risk for complications of GERD and reassuring parents of patients with physiologic GER who are not at risk for complications to avoid unnecessary diagnostic procedures or pharmacologic therapy. [62][63][64] …”
Section: Discussionmentioning
confidence: 99%
“…It cannot be overemphasized that pediatric best practice involves both identifying children at risk for complications of GERD and reassuring parents of patients with physiologic GER who are not at risk for complications to avoid unnecessary diagnostic procedures or pharmacologic therapy. [62][63][64] …”
Section: Discussionmentioning
confidence: 99%
“…Acid reflux in a child with chronic cough does not necessarily mean causality. A recent study showed that nearly 90% of cough spells in children did not correspond with a reflux event documented by pH probe 40. Weakly acid and non-acid reflux has been proposed as causal.…”
Section: Reflux-related Coughmentioning
confidence: 99%
“…Twenty-one of 26 children (75%) with a history of asthma had positive esophageal biopsies. Using a specially designed pH probe, Chang et al [34 ] found that, of 5628 coughs recorded in 20 children over a 24-h period, 83.9% were independent of a reflux event.…”
Section: Laryngopharyngeal Refluxmentioning
confidence: 99%